METHODOLOGY FOR EVALUATION OF SOUND POWER LEVELS IN WOODWORKING MILLING MACHINES (Innovation in Woodworking Industry and Engineering design, 2026)
Woodworking machines belong to the noisiest working machinery that requires study and analysis of noise characteristics in order to reduce the levels of noise emissions. Noise generation is a complex process that depends on the design features and technical characteristics of the machine and its cutting tools, on one hand and the cutting process and the type of material to cut, on the other. Generated noise can be categorized as idling noise and cutting noise, depending on the working process and each one of them has to be assessed and analyzed independently. The objective of the current study is to present a methodology for evaluation of sound power levels, generated by woodworking milling machines, assessed by measuring the sound pressure levels.